Effectiveness of Self Management in Reducing Truancy Behavior of High School Students in Bandar Lampung - Masya, Hardiyansyah; Kamil, Badrul (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2019)
The phenomenon of disciplinary problems of the student  is still happen. Discipline behavior is a behavior that demonstrates obedience and compliance which requires students to comply with established regulations. One of the most frequent disciplinary violations is leaving school without permission. Several factors that influence students to break discipline are environmental factors. Therefore, it needs proper handling in overcoming discipline problems of students. one technique that can be used in overcoming disciplinary problems, namely self-management. In the use of self management techniques to overcome undisciplined behavior students are directed to modify environmental aspects that can influence the emergence of undisciplined behavior.